Research on Traffic Identification Based on Multi Layer Perceptron - Dingding Zhou; Wei Liu; Wengang Zhou; Shi Dong (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
In order to solve some problems of traffic identification, this paper presents a multi-layer neural network-based method for traffic identification, and multi-layer neural network parameters are analyzed, experimental results show that this method can effectively solve some problems, and can improve the classification correctness.